Answer:
X = 46
Step-by-step explanation:
X + 43 + 35 + 56 =180
X + 134 = 180
X = 180 - 134
X = 46
First answer (x=-2)
...
(2)[(-2)^2]+6-20
2(4)+6-20
8+6-20
14-20
<em>-6 (answer)
</em><em>
</em><em />Second answer (x=5)
...
(2)[(-5)^2]+6-20
2(25)+6-20
50+6-20
56-20
<em>36 (answer)
</em>Hope this helps!
Answer:
58
Step-by-step explanation:
1. let x be the unknown number
2. make an expression
x + 26/12 = 7/1
3. cross multiply
x +26 × 1 = x + 26
12 × 7 = 84
x + 26 = 84
4. move variables on one side and numbers on other side of the equal sign
x + 26 = 84
- 26 -26
x = 58
Answer:
0.9958
Step-by-step explanation:
P(being correct) = 1/4 = 0.25
Hence, p = 0.25
n = 19
P(x ≥ 1) = p(x = 1) + p(x = 2) +... + p(x = 19)
Using the binomial probability formula :
P(x =x) = nCx * p^x * (1 - p)^(n - x)
However, to save computation time, we could use a calculator :
Using a calculator,
P(x ≥ 1) = 0.99577
P(x ≥ 1) = 0.9958
Answer:
y=h(x)-8
Step-by-step explanation:
it shifted down 8 units